2017
DOI: 10.3389/fphar.2017.00636
|View full text |Cite
|
Sign up to set email alerts
|

Food and Sex-Related Impacts on the Pharmacokinetics of a Single-Dose of Ginsenoside Compound K in Healthy Subjects

Abstract: Background and Objectives: Ginsenoside compound K (CK) is a candidate drug for rheumatoid arthritis therapy. This clinical trial was designed to evaluate the effects of food and sex on the pharmacokinetics of CK and its metabolite 20(S)-protopanaxadiol (PPD).Methods: An open-label, single-center, two-period crossover trial was performed in healthy Chinese subjects (n = 24; male = 12, female = 12), randomized to either the fasting overnight or the high-fat meal group before a single 200 mg dose of monomer CK wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 44 publications
1
28
0
Order By: Relevance
“…Unfortunately, due to the difficulties in distinguishing intestinal segments and inconsistency among protein levels, mRNA levels, and activities, the sex-related expression of transporters in the intestine still remains controversial (MacLean et al, 2008 ; Mariana et al, 2011 ). Another phenomenon that we could observe from these two trials was that food can significantly increase the absorption of CK, which was consistent with the results from another independent clinical trial (Chen et al, 2017 ). The exact mechanism for the increased ginsenoside CK exposure in the presence of a high-fat meal is still unknown and may be the result of increasing solubilization and dissolution in the intestinal fluids, especially, for the drugs with poor water solubility (Welling, 1996 ).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Unfortunately, due to the difficulties in distinguishing intestinal segments and inconsistency among protein levels, mRNA levels, and activities, the sex-related expression of transporters in the intestine still remains controversial (MacLean et al, 2008 ; Mariana et al, 2011 ). Another phenomenon that we could observe from these two trials was that food can significantly increase the absorption of CK, which was consistent with the results from another independent clinical trial (Chen et al, 2017 ). The exact mechanism for the increased ginsenoside CK exposure in the presence of a high-fat meal is still unknown and may be the result of increasing solubilization and dissolution in the intestinal fluids, especially, for the drugs with poor water solubility (Welling, 1996 ).…”
Section: Discussionsupporting
confidence: 91%
“…This work and what we've already published (Chen et al, 2017 ) both belong to phase I clinical trials of Ginsenoside Compound K Tablets (Hisun Pharmaceutical Co., Ltd, Taizhou, China), but they are completely independent trials. More concretely, these two studies were performed on different subjects through different designs for different purposes.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Our previous research has shown that GCK is safe and well-tolerated for healthy Chinese volunteers, where it exhibits a good pharmacokinetic profiles at a moderate dose ( Chen et al, 2018 ). Its pharmacokinetic properties are affected by food and gender in humans ( Chen et al, 2017 ). These findings indicated that GCK has a promising druggability that provides guidance for the development of CK.…”
Section: Introductionmentioning
confidence: 99%